Small nuclear ribonucleoproteins of Drosophila: identification of U1 RNA-associated proteins and their behavior during heat shock. - Wieben, E D (1982)
In Drosophila, two nuclear proteins of approximately 26,000 and 14,000 molecular weight are recognized by a human autoimmune antibody for mammalian ribonucleoprotein (RNP) particles that contain U1 small nuclear RNA. The antibody-selected Drosophila RNP contains, in addition to these two proteins, a single RNA species that has been identified as U1 by hybridization with a cloned Drosophila U1 DNA probe. Small nuclear RNP isolated from human cells under the same conditions as used for Drosophila and selected by the anti-U1 RNP-specific antibody contains eight proteins, two of which are similar in molecular weight to the two Drosophila U1 RNP proteins. Thus, even though the nucleotide sequences of Drosophila and human U1 RNA are about 72% homologous, and the corresponding RNPs are both recognized by the same human autoantibody, Drosophila U1 RNP appears to have a simpler protein complement than its mammalian counterpart. The two Drosophila U1 RNA-associated proteins are synthesized at normal or slightly increased rates during the heat shock response and are incorporated into antibody-recognizable RNP complexes. This raises the possibility that U1 RNP is an indispensable nuclear element for cell survival during heat shock.